Dynamics of above- and belowground responses of silver birch saplings and soil gases to soil freezing and waterlogging during dormancy. (13th January 2021) - Repo, Tapani; Domisch, Timo; Roitto, Marja; Kilpeläinen, Jouni; Wang, Ai-Fang; Piirainen, Sirpa; Heiskanen, Juha; Makita, Naoki; Lehto, Tarja; Sutinen, Sirkka
Abstract: Winter precipitation and soil freeze–thaw events have been predicted to increase in boreal regions with climate change. This may expose tree roots to waterlogging (WL) and soil freezing (Fr) more than in the current climate and therefore affect tree growth and survival. Using a whole-tree approach, we studied the responses of silver birch ( Betula pendula Roth.) saplings, growing in mineral soil, to 6-week Fr and WL in factorial combinations during dormancy, with accompanying changes in soil gas concentrations. Physiological activation (dark-acclimated chlorophyll fluorescence and chlorophyll content index) and growth of leaves and shoot elongation and stem diameter growth started earlier in Fr than NoFr (soil not frozen). The starch content of leaves was temporarily higher in Fr than NoFr in the latter part of the growing season. Short and long root production and longevity decreased, and mortality increased by soil Fr, while there were no significant effects of WL. Increased fine root damage was followed by increased compensatory root growth. At the beginning of the growing season, stem sap flow increased fastest in Fr + WL, with some delay in both NoWL (without WL) treatments. At the end of the follow-up growing season, the hydraulic conductance and impedance loss factor of roots were higher in Fr than in NoFr, but there were no differences in above- and belowground biomasses. The concentration of soil carbon dioxide increased and methane decreased by soil Fr at the end of dormancy. At the beginning of the growing season, the concentration of nitrous oxide was higher in WL than in NoWL and higher in Fr than in NoFr. In general, soil Fr had more consistent effects on soil greenhouse gas concentrations than WL. To conclude, winter-time WL alone is not as harmful for roots as WL during the growing season.